Women's migration to and from some Mediterranean countries in Vientos de agua by Juan José Campanella - Sánchez, Mariela Paula (2022)
This article tries to highlight the particular features that migrant women show in a pioneering cultural product: Juan José Campanella´s television series Vientos de agua (Water Winds), 2005. The process of forced geographical displacement is situated during two terms: the middle of the 20th century and the beginning of the 21st century. Women who fled from Mediterranean Europe to America, moving away from fascism in different Mediterranean latitudes, and women who, years after, seek in Spain a subsistence not guaranteed in their places of origin, share similar miseries in the process of leaving homeland. The intention of these lines is to give account of their vulnerabilities and the reason why is relevant to focus on them.